Trichoderma Ganoderma disease control in oil palm : a manual - Virdiana, Ike (Techniques in plantation science series., 2019)
This manual describes methods for isolating Trichoderma from the wild, in vitro culture methods, assessing virulence in combating Ganoderma, commercial production and application to the soil during field planting of nursery-produced oil palm plants. The manual is one in a series of manuals on Techniques in Plantation Science and has direct relevant links with other manuals in the series, particularly: Nursery Practices in Oil Palm, Field Trialling in Oil Palm and Nursery Screening for Ganoderma Response in Oil Palm Seedlings. Target audiences are students and researchers in agriculture, plant pathology, agronomy, growers and end-users interested in the practicalities of sustainable oil palm production. It provides a resource for training, a knowledge base for those new to oil palm and a reference guide to managers, particularly if they are interested in increasing the sustainability of their production.